Placental mRNA in maternal plasma as a predictor of ectopic pregnancy - Takacs, Peter (2012)
OBJECTIVE: To measure and compare placental mRNA expression in the maternal circulation among women with intrauterine and ectopic pregnancies. METHODS: Plasma was collected from patients in early pregnancy at risk of ectopic pregnancy. Clinical information was prospectively collected and entered into a dedicated database. mRNA was isolated from maternal plasma and quantitative RT-PCR was performed to measure mRNA for human gonadotropin (hCG) and human placental lactogen (hPL). GAPDH mRNA expression was used as an internal control. RESULTS: Twelve women with ectopic pregnancy and 13 women with intrauterine pregnancy were enrolled. Patients with ectopic pregnancy were 6 times more likely to have undetectable levels of hPL mRNA (relative risk [RR] 6.36; 95% confidence interval [CI], 1.70–23.20; P<0.01). They were also 8 times more likely to have undetectable levels of hCG mRNA (RR 8.64, 95% CI, 1.30–57.10; P<0.01). mRNA copy numbers for hPL and hCG (normalized by GAPDH) were significantly lower in the ectopic group than in the intrauterine group. CONCLUSION: Placental mRNA is present in the maternal circulation in significantly lower copies in cases of ectopic pregnancy compared with cases of intrauterine pregnancy. Measurement of placental mRNA in the maternal circulation may help to distinguish between intrauterine and ectopic pregnancies.